The spectrum of person-centered care: from luxury to necessity: a descriptive qualitative study - Noushin Mousazadeh; Faezeh Babaieasl; Samaneh Bagherian; Sogand Mivehchi (BMC Nursing)
Abstract Background Person-centered care (PCC) constitutes a fundamental element of holistic nursing practice, emphasizing patient engagement and comprehensive understanding beyond pathology. This study sought to investigate nurses’ perceptions of PCC within the Iranian healthcare system. Given the aging population in Iran, ongoing challenges in implementing PCC in clinical practice, and the limited qualitative research on this topic, understanding nurses’ perspectives is crucial for improving care delivery. Methods A descriptive qualitative content analysis study was employed, conducted in 2024 at public hospitals in northern Iran. Sixteen nurses from diverse clinical departments were recruited via purposive sampling. Data collection utilized semi-structured interviews, with subsequent analysis performed through conventional content analysis using MAXQDA 10 software, adhering to Graneheim and Lundman’s analytical framework. Results Analysis yielded one overarching theme, “Luxurious or Necessary,” comprising two categories: “Luxurious care” and “Enriched nursing care.” Eight subcategories emerged: being supportive, being heard, being compassionate, individualized care, care with competence, care with commitment, care with conscience, and care with respect. These were derived from 850 initial codes. Conclusion Findings indicated a dichotomous perspective among nurses regarding PCC, with some considering it essential to quality care, while others perceived it as a superfluous formality. This divergence in viewpoints underscores the imperative for healthcare policymakers to formulate and implement strategies that enhance nurses’ comprehension and application of PCC principles, thereby fostering improved community health outcomes. Clinical trial number Not applicable.